Effectiveness of Silica Humate in Improving Soil Quality in Paddy Field Contaminated by Industrial Waste - Nanda Ajeng Kartika; Wanti Mindari; Siswanto Siswanto; M. Ghufron Chakim (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Soil degradation caused by industrial waste in Sidoarjo Regency has led to a decline in agricultural productivity, necessitating soil rehabilitation efforts. This study aimed to evaluate the effectiveness of silica humate as a soil amendment on paddy fields contaminated by industrial waste. The experiments were arranged according to the Factorial Complete Randomized Design, where the first factor: 3 kinds of industrial waste namely the pharmaceutical, livestock feed, and paper industry. Second factor; 5 doses of silica humat (0, 10, 20, 30, and 40 kg/ha). The parameters included soil pH, cation exchange capacity (CEC), total nitrogen (total-N), and available phosphorus (available-P), measured at 14 and 56 days after application (DAA). Results showed that the effectiveness of silica humate varied depending on the type of industrial waste and increased over time. On land contaminated with pharmaceutical waste, silica humate increased CEC from 44.34 to 52.52 cmol(+)/kg and available-P from 27.21 to 36.69 ppm at low doses. Land contaminated with animal feed waste showed the best results at a dose of 20 kg/ha, while land contaminated with paper industry waste required higher doses. These findings suggest that silica humate is promising as a viable soil amendment strategy, though optimal dosage rates must be tailored to specific industrial contamination types for maximum rehabilitation effectiveness.